Analysis Of Consumer Preferences Towards The Decision To Purchase Thrifting Products In Surakarta City - Alfito Akbar Wibisono; Kussudyarsana Kussudyarsana (Jurnal Economic Resource, 2026)
This study applies a quantitative research approach aimed at testing hypotheses through numerical data obtained from a Likert scale questionnaire (1–5). The data were analyzed using classical assumption tests and multiple linear regression analysis with the assistance of SPSS version 26. The research was conducted in Surakarta City starting in November 2024, involving 100 respondents who had experience purchasing thrifting products. The sample was selected using a non-probability sampling method with a purposive sampling technique, focusing on consumers domiciled in Surakarta City who had purchased thrifting products. The results indicate that brand image and product quality have a positive and significant effect on purchasing decisions, while price perception and design have a negative and significant effect on purchasing decisions. These findings suggest that strengthening brand image and product quality is essential, while pricing strategies and design preferences must be carefully aligned with consumer expectations in the thrifting market.